Non-linear model predictive control to improve transient production of a hot dip galvanising line. (8th August 2016) - Wu, H.; Speets, R.; Ozcan, G.; Ekhart, R.; Heijke, R.; Nederlof, C.; Boeder, C.J.
Abstract : A numerical transient model was designed to describe the dynamics of the annealing process prior to coating in a hot dip galvanising (HDG) line. The model was integrated into a model predictive controller developed in a previous work, including an adaptation mechanism to retain the model accuracy in operation. Complex transient production was studied to formulate proper constraints as input for the optimisation problem to be solved in real time. Simulations and online tests were carried out to verify the transient model and the controller design principles. The new controller has been implemented on a HDG line which annually produces 400 000 t of coated strip products mainly for the automotive and construction markets. Production using this controller proves its ability to correctly predict the future operation and optimise the control automation of the heating, the cooling and the line speed. Detailed data analysis shows significant improvements in terms of strip transition control precision, temperature control accuracy (50% increase inside tolerances), throughput maximisation (3–8% increase) and production consistency through the full automation.